2020
DOI: 10.1002/smll.202003916
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on NiFe‐Based Electrocatalysts for the Oxygen Evolution Reaction

Abstract: are required. [2a,b,3] Among the various sustainable energy candidates, hydrogen fuel has garnered significant attention owing to its natural advantages. Hydrogen is typically a nontoxic and environmentally friendly power source that can be produced from water, which is an earth-abundant reactant, and produces no CO 2 emissions when converted into other energy forms. [4-6] In addition, due to its high mass-specific energy density, hydrogen can be efficiently used in mobile applications. Moreover, hydrogen can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
137
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(137 citation statements)
references
References 207 publications
(268 reference statements)
0
137
0
Order By: Relevance
“…These technologies can provide a zero-carbon solution to convert intermittent renewable energy, including solar and wind power, into chemical energy stored in fuels or chemicals, thereby reducing our dependence on fossil fuels. Unfortunately, OER remains a major bottleneck for practical application due to its sluggish kinetics involving four-electron transfer, [1] although various electrocatalysts, including some noble metal oxides (RuO 2 and IrO 2 ), [2] layered double (oxy) hydroxides, [3] and perovskites, [4] have been developed to facilitate the electron transfer. Compared with other catalysts, Ni-Fe layered double hydroxide (NiFe-LDH) has a competitive advantage because of the high availability on the earth and the high activity in alkaline electrolytes, [5] but the deficiency in rational design for exposing more active sites greatly hinders the further improvement of its OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…These technologies can provide a zero-carbon solution to convert intermittent renewable energy, including solar and wind power, into chemical energy stored in fuels or chemicals, thereby reducing our dependence on fossil fuels. Unfortunately, OER remains a major bottleneck for practical application due to its sluggish kinetics involving four-electron transfer, [1] although various electrocatalysts, including some noble metal oxides (RuO 2 and IrO 2 ), [2] layered double (oxy) hydroxides, [3] and perovskites, [4] have been developed to facilitate the electron transfer. Compared with other catalysts, Ni-Fe layered double hydroxide (NiFe-LDH) has a competitive advantage because of the high availability on the earth and the high activity in alkaline electrolytes, [5] but the deficiency in rational design for exposing more active sites greatly hinders the further improvement of its OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that the interlaminar basal plane of bulk NiFe-LDH is conducive to OER activity. However, the slow diffusion of proton receptors (such as OH − ) in the interlaminar NiFe-LDH during the OER process leads to the dissolution of NiFe-LDH, thus reducing OER activity over time [26,29]. Therefore, exposing more active specific surface areas and improving the stability of NiFe-LDH are effective methods to further enhance their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen evolution reaction (OER) is one of the most basic and important electrochemical reactions for the production of renewable energy, which can be used in many green energy systems such as water splitting, fuel cells and metal-air batteries [1,2]. The multi-electron transfer reaction mechanism makes it challenging to develop such highly efficient catalysts [3,4]. Noble metals oxides (RuO 2 /IrO 2 ) have been used as OER catalysts in practical applications [5,6].…”
Section: Introductionmentioning
confidence: 99%